PENYULUHAN GEMAR MENABUNG UNTUK MASA DEPAN YANG CERAH DI SMP NEGERI KELURAHAN HARAPAN JAYA - KOTA BEKASI - Bintang Narpati; Indra Lubis; Kardinah Indriana Meutia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
Saving is the first step in facing a better future for a prosperous life. To achieve this goal, from an early age, it is better if children who are studying in elementary school or kindergarten are taught to like to save money. You don't need a lot of money to save in the savings place, but only enough to set it aside from the smallest nominal, for example Rp. 500, - (five hundred rupiah) first because according to research (Furnham, 1999) that more than 80% of children claim their parents will not give them extra money if they spend it all. This requires saving activities for children. Why saving for early childhood does not require large funds, in this case, the main point of saving is to foster a feeling of being fond of saving since childhood. Why is it done in early childhood? because by doing these habits will foster adult habits later to always save in any circumstances. The form of activities carried out at Community Service (PKM) is in the form of counseling to the children of SMPN 5 kota Bekasi City for grades 1, 2 and 3. The counseling is in the form of an appeal to these children to set aside money if they are given pocket money by their parents . This is done is by providing an example of how to save by carrying a piggy bank that is easy to buy in bookstores or others. Some are made of plastic, cans or fabric. In essence, saving is by setting aside